Maximal oxygen consumption in college students is reliable following four consecutive trials - Romero Fallas, Oscar (2012)
The purpose of the study was to determine the reliability of the maximal oxygen consumption (VO2max) following four consecutive trials with 10 min rest between trials using the Bruce protocol. Participants were 16 apparently healthy college students (7 females, 9 males), who performed the Bruce protocol and after reaching their VO2max stepped down the treadmill and rested seated on a chair during 10 min. These procedures were repeated three consecutive times. Results indicated no significant differences in mean VO2max values between trials (p > 0.05), although gender differences were found (Females = 40.77 ± 1.95 ml/kg/min vs. Males = 50.77 ± 1.72 ml/kg/min; p = 0.002). Reliability was determined by the intraclass correlation coefficient (ICC), indicating a high reproducibility in the VO2max values between trials (rICC = 0.96, CI95% = 0.92, 0.98). No adverse effects were reported during the 10 min rest between trials. In conclusion, resting 10 min between maximal Bruce protocol treadmill tests does not affect VO2max in young healthy participants. It is feasible and reliable to perform maximal treadmill tests in a single session without adverse effects for the participant.